Effect of acupuncture on patients with major psychiatric disorder and related symptoms caused by earthquake exposure: Protocol for a scoping review of clinical studies. - Hui-Ju Kwon; Jungtae Leem; Da-Woon Kim; Chan-Young Kwon; Sang-Ho Kim (PLoS ONE)
Earthquakes have the greatest destructive effect among all natural disasters. Posttraumatic stress disorder (PTSD), major depressive disorder (MDD), and anxiety disorder (AD) are major psychiatric disorders (MPD) that can be triggered by exposure to earthquakes. Conventional treatments such as pharmacological treatments have several limitations. Acupuncture therapy as a complementary integrative medicine may be an effective alternative treatment for these limitations. This study aimed to identify the status of the clinical evidence regarding acupuncture therapy for earthquake survivors with MPD. We will follow the scoping review process as previously described. The study question is as follows: "Which types of clinical research designs, study types, study durations, adverse events, and clinical outcomes have been reported regarding acupuncture therapy for MPD in earthquake survivors?" Medline, Excerpta Medica dataBASE, Cochrane Central Register of Controlled Trials, Web of Science, Scopus, Allied and Complementary Medicine Database, Cumulative Index to Nursing and Allied Health Literature, PsycArticles databases, and Chinese, Korean, and Japanese databases will be comprehensively searched electronically from their inception to November 2022. Data from the included studies will be collected and descriptively analyzed in relation to our research question. We will collate, synthesize, and summarize the extracted data according to the analytical framework of a scoping review. The protocol will conform with the Preferred Reporting Items for Systematic Reviews and Meta-Analyses Extensions of Scoping Reviews to ensure the clarity and completeness of our reporting in the whole phase of the scoping review (Protocol registration: https://osf.io/wfru7/). The findings of this scoping review will provide fundamental data that will help researchers identify appropriate research questions and design further studies on the use of acupuncture for MPD management in earthquake survivors. These results will be helpful for developing disaster site-specific research protocols for future clinical trials on this topic.